Effects of altitude and harvesting dates on morphological characteristics, yield and nutritive value of desho grass (Pennisetum pedicellatum Trin.) in Ethiopia - Asmare, Bimrew; Demeke, Solomon; Tolemariam, Taye; Tegegne, Firew; Haile, Aynalem; Wamatu, Jane (Agriculture and Natural Resources, 2017)
The effects of altitude and harvesting period on the performance of desho grass were evaluated in Ethiopia. A factorial arrangement of treatments was employed with a combination of two altitudes and three harvesting dates. Planting and management of desho grass was undertaken according to recommendations for the species. The data collected consisted of plant height, number of tillers, number and length of leaves, leaf-to-stem ratio and fresh yield. Chemical analysis of the constituents of desho grass samples was completed according to standard procedures. All data were subjected to two analysis of variance procedures and Pearson correlation analysis, with significance tested at p < 0.05. Results indicated that most morphological characteristics were not significantly different due to altitude except the leaf length per plant. Harvesting dates significantly affected the number of leaves per plant, leaf-to-stem ratio and dry matter yield. Both altitude and harvesting date significantly affected the crude protein content, yield and fiber fractions. Calcium content was significantly different only regarding harvesting date and phosphorus content was significantly affected by altitude. Dry matter content and yield were positively correlated with parameters such as plant height, leaf length per plant, crude protein (CP) yield, fiber fractions (neutral detergent fiber and acid detergent fiber) and with each other. Crude protein content was positively correlated with the CP yield. Overall results indicated that desho grass was affected more by harvesting date than altitude. Generally, desho grass performed well both at mid and high altitude in Ethiopia and could be a potential livestock feed in the country